2021
DOI: 10.17826/cumj.993832
|View full text |Cite
|
Sign up to set email alerts
|

İntihar girişimi nedeniyle acil servise başvuran olguların incelenmesi: bir yıllık retrospektif bir çalışma

Abstract: Amaç: Bu çalışmada intihar girişimi nedeniyle acil servise başvuran olguların intihar girişiminden önceki son bir yıldaki özelliklerinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Retrospektif tipte yapılan çalışma kapsamında bir eğitim ve araştırma hastanesi acil servisine 1 Ağustos 2018-1 Ağustos 2019 tarihleri arasında İntihar girişimi ile başvuran 135 hastanın dosyası incelendi. Çalışmanın verileri veri toplama formu aracılığıyla hastane kayıtları üzerinden toplandı. Bulgular: Hastaların yaş … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is extremely important to be able to empathize, be understanding and objective, and give hope and confidence in the approach to these patients (2,5,16) . It was reported that patients apply to hospitals for various reasons before attempting suicide, the most frequently applied area is the emergency department, and patients who have attempted suicide has an increased probability to attempt again (17) . It is necessary for the nurses to identify the cases applying to the emergency department because of suicide attempts, to be directed to the psychiatry clinics to receive psychiatric care, and to be followed up there.…”
Section: Introductionmentioning
confidence: 99%
“…It is extremely important to be able to empathize, be understanding and objective, and give hope and confidence in the approach to these patients (2,5,16) . It was reported that patients apply to hospitals for various reasons before attempting suicide, the most frequently applied area is the emergency department, and patients who have attempted suicide has an increased probability to attempt again (17) . It is necessary for the nurses to identify the cases applying to the emergency department because of suicide attempts, to be directed to the psychiatry clinics to receive psychiatric care, and to be followed up there.…”
Section: Introductionmentioning
confidence: 99%